1998
DOI: 10.1097/00006534-199811000-00047
|View full text |Cite
|
Sign up to set email alerts
|

Cranioplasty with Neovascularized Autogenous Calvarial Bone

Abstract: We have presented two cases of cranioplasty with neovascularized autogenous calvarial bone. A surgical procedure applying the principle of flap prefabrication has been applied to the preservation of autogenous calvarial bone obtained during external cranial decompression. The rectus abdominis muscle flap was elevated. A subcutaneous pocket was prepared for preservation of calvarial bone integrated with the rectus abdominis muscle. The outer cortex of calvarial bone was removed partially by bone chiseling. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Resorptive processes of various degrees are unavoidable in all the clinical procedures mentioned (Li et al, 2005). From the biological standpoint the reintegrated skull bone is an osteoconductive, nonperfused implant that will be remodelled by the surrounding tissues (Tsukagoshi et al, 1998). Remodelling is a process, which can lead to full resorption of the autogenous bone material.…”
Section: Discussionmentioning
confidence: 99%
“…Resorptive processes of various degrees are unavoidable in all the clinical procedures mentioned (Li et al, 2005). From the biological standpoint the reintegrated skull bone is an osteoconductive, nonperfused implant that will be remodelled by the surrounding tissues (Tsukagoshi et al, 1998). Remodelling is a process, which can lead to full resorption of the autogenous bone material.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the concept of skull flap cryopreservation has been present for at least six decades 3 . Intuitively, the use of autogenous bone flap for delayed cranioplasty represents a logical choice, offering a biological and exact reconstruction of the skull defect with the potential for engraftment, remodelling and growth 9 . Furthermore, the additional costs of alloplastic substitutes and risks of foreign body reaction/rejection are avoided.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47][48][49] Çelik et al 45 observed that prefabricated bone showed histological characteristics similar to those seen in normal bone after 12 months in rabbits. In a histological study of bone prefabrication using a rat model, Gill et al 46 observed that the original bone was dead but extensive new bone formation was visible 3 weeks after implantation, whereas newly formed bone had progressed after 6 weeks.…”
Section: Discussionmentioning
confidence: 90%
“…47,48 Tsukagoshi et al 47 sutured the cranial bone graft onto the rectus abdominis muscle and transferred the integrated bonemuscle complex to the cranium using a microsurgical technique after a delay period. We prefabricated the cranial bone inside the adjacent tissue and prepared a local flap during the subsequent operation.…”
Section: Discussionmentioning
confidence: 99%